Myoimaging in the NGS era: the discovery of a novel mutation in MYH7 in a family with distal myopathy and core-like features – a case report. Issue 1 (December 2016) - Astrea, Guja; Petrucci, Antonio; Cassandrini, Denise; Savarese, Marco; Trovato, Rosanna; Lispi, Ludovico; Rubegni, Anna; Giacanelli, Manlio; Massa, Roberto; Nigro, Vincenzo; Santorelli, Filippo
Abstract Background Myosin heavy chain 7 related myopathies are rare disorders characterized by a wide phenotypic spectrum and heterogeneous pathological features. In the present study, we performed clinical, morphological, genetic and imaging investigations in three relatives affected by autosomal dominant distal myopathy. Whilst earlier traditional Sanger investigations had pointed to the wrong gene as disease causative, next-generation sequencing allowed us to obtain the definitive molecular genetic diagnosis in the family. Case presentation The proposita, being found to harbor a novel heterozygous mutation in theRYR1 gene (p.Glu294Lys), was initially diagnosed with core myopathy. Subsequently, consideration of muscle magnetic resonance imaging (MRI) features and extension of family study led this diagnosis to be questioned. Use of next-generation sequencing analysis identified a novel mutation in theMYH7 gene (p.Ser1435Pro) that segregated in the affected family members. Conclusions This study identified a novel mutation inMYH7 in a family where the conclusive molecular diagnosis was reached through a complicated path. This case report might raise awareness, among clinicians, of the need to interpret NGS data in combination with muscle MRI patterns so as to facilitate the pinpointing of the main molecular etiology in inherited muscle disorders.